Atmospheric Electricity Influencing Biogeochemical Processes in Soils and Sediments - Hunting, Ellard R.; Harrison, R. Giles; Bruder, Andreas; van Bodegom, Peter M.; van der Geest, Harm G.; Kampfraath, Andries A.; Vorenhout, Michel; Admiraal, Wim; Cusell, Casper; Gessner, Mark O. (Frontiers in Physiology, 2019)
The Earth surface represents a complex electrochemical environment that consists of many electro-active charged chemical compounds that are relevant for many biological processes. During the day and over seasons, concentrations of various many of these chemical compounds are known to fluctuate within Earth’s surface environments. This has been observed for surface waters, their sediments and continental soils. This variability can particularly affect small, relatively immobile organisms that live within these environments. While various drivers of spatio-temporal variability have already been recognized, a comprehensive understanding is still lacking. Here we propose that variations in Aatmospheric electricity can influence the electrochemical environments of water bodies, soils and sediments, with implications for organisms and in turn ecosystem processes. This mechanism is likely relevant for a wide range of organisms. We tested this mechanism in field- and laboratory-based case studies. Measuring subsurface redox conditions in outdoor soils and sediment, we found evidence for both local and global variations in atmospheric electricity with coinciding patterns in subsurface redox conditions. In the laboratory, bacterial respiratory responses, electron transport activity and H2S production were observed to follow changes in atmospheric cation concentrations. We argue that such mechanisms are part of an overlooked concept that may help to explain the frequently observed spatio-temporal fluctuations, and therewith significantly widens our conceptual understanding of chemical and biological processes in the Earth’s surface and their interactions with the atmospheric and physical environment.